2002
DOI: 10.1111/1467-9280.00484
|View full text |Cite
|
Sign up to set email alerts
|

Infant Timekeeping: Attention and Temporal Estimation in 4-Month-Olds

Abstract: Four-month-old infants were exposed to sequences in which a 2-s light stimulus alternated with dark interstimulus periods whose length was manipulated to be 3 or 5 s. A predictable on-off pattern occurred for eight trials, but the light stimulus was omitted on the ninth trial. Infants showed heart rate responses on the omission trial that were closely synchronized with the expected recurrence of the stimulus. In addition, these heart rate patterns were observed predominantly in infants who had previously shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
1
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 45 publications
1
39
1
1
Order By: Relevance
“…A series of innovative studies of timing in infancy have demonstrated infants' sensitivity to the duration of events and the developmental continuity of the processes involved in time perception (e.g., Brannon et al, 2004;Colombo & Richman, 2002;VanMarle & Wynn, 2006). Moreover, research with older children, much of which has been conducted by Sylvie Droit-Volet, has carefully charted developmental improvements in sensitivity to duration and also identified some of the mechanisms that contribute to such improvements (see Droit-Volet, 2013.…”
Section: Time As a Dimension: Processing Durationmentioning
confidence: 99%
“…A series of innovative studies of timing in infancy have demonstrated infants' sensitivity to the duration of events and the developmental continuity of the processes involved in time perception (e.g., Brannon et al, 2004;Colombo & Richman, 2002;VanMarle & Wynn, 2006). Moreover, research with older children, much of which has been conducted by Sylvie Droit-Volet, has carefully charted developmental improvements in sensitivity to duration and also identified some of the mechanisms that contribute to such improvements (see Droit-Volet, 2013.…”
Section: Time As a Dimension: Processing Durationmentioning
confidence: 99%
“…In addition to being sensitive to various forms of temporal information, infants can use the passage of time to anticipate a change in the temporal distribution of stimulation (Clifton 1974;Brooks and Berg 1979;Donohue and Berg 1991;Colombo and Richman 2002) and can form expectations based on the temporal distribution of stimulation as early as 2 months of age (Canfield and Haith 1991). Moreover, the earlyappearing ability to predict the future occurrence of visual stimulation is positively linked to childhood full-scale IQ at 46 months of age (Dougherty and Fig.…”
Section: Perception Of Temporal Information In Infancymentioning
confidence: 99%
“…This has also been widely demonstrated in studies of animals and infants who are capable of estimating temporal intervals despite a lack of temporal reasoning ability. For example, in classical temporal conditioning paradigms, infants automatically react (e.g., pupillary dilatation, heart rate deceleration) to the omission of an event presented at regular intervals (e.g., Brackbill & Fitzgerald, 1972;Colombo & Richman, 2002). Other studies using the standard habituation procedure have also observed infants' reactions to differences in the presentation duration of events (Brannon, Libertus, Meck, & Woldorff, 2008;Brannon, Roussel, Meck, & Woldorff, 2004;De Hevia, Izard, Coubart, Spelke, & Streri, 2014;VanMarle & Wynn, 2006).…”
Section: Introductionmentioning
confidence: 99%